2019
DOI: 10.1364/ol.44.002986
|View full text |Cite
|
Sign up to set email alerts
|

Intra-pulse difference-frequency generation of mid-infrared (27–20  μm) by random quasi-phase-matching

Abstract: We present a mid-infrared (MIR) source based on intrapulse difference-frequency generation under the random quasi-phase-matching condition. The scheme enables the use of non-birefringent materials whose crystal orientations are not perfectly and periodically poled, widening the choice of media for nonlinear frequency conversion. With a 2 μm driving source based on a Ho:YAG thin-disk laser, together with a polycrystalline ZnSe element, an octavespanning MIR continuum (2.7-20 μm) was generated. At over 20 mW, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 29 publications
(49 reference statements)
0
24
1
Order By: Relevance
“…RQPM is costless and independent to material orientation and input laser polarization, thus it possesses an extremely large bandwidth. During the past few years, RQPM nonlinear interactions driven by femtosecond lasers have received increasing attention to get broadband coherent mid-infrared (MIR) laser sources [2][3][4][5][6]. The RQPM efficiency can be comparable to traditional PM and QPM methods [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RQPM is costless and independent to material orientation and input laser polarization, thus it possesses an extremely large bandwidth. During the past few years, RQPM nonlinear interactions driven by femtosecond lasers have received increasing attention to get broadband coherent mid-infrared (MIR) laser sources [2][3][4][5][6]. The RQPM efficiency can be comparable to traditional PM and QPM methods [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, RQPM nonlinear interactions driven by femtosecond lasers have received increasing attention to get broadband coherent mid-infrared (MIR) laser sources [2][3][4][5][6]. The RQPM efficiency can be comparable to traditional PM and QPM methods [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Random quasi-phase matching (RQPM) nonlinear optical frequency conversion that occurs in disordered polycrystalline nonlinear medium is under increasing attention, as it neither requires a specific material orientation nor depends on a certain polarization combination [1]- [6]. The most representative material is ZnSe, a cubic-symmetry semiconductor with broad transparency from visible to long-wave infrared (IR), high second-order nonlinearity and excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The optical parametric oscillator (OPO) based on polycrystalline ZnSe was achieved pumping by mode-locked Cr:ZnS laser pulses, generating broadband spectrum spanning 3-7.5 μm [2], [3]. Pumping with a Ho:YAG thin-disk femtosecond laser, ultra-broadband MIR continuum from 2.7 to 20 μm was also realized in polycrystalline ZnSe via intra-pulse difference frequency generation (DFG) [6]. Experimental results have shown that the RQPM efficiency can be comparable to traditional phase matching (PM) in birefringent crystals and QPM in periodically inverted crystals [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…One particular type of DFG process known as intra-pulse DFG (IDFG) has shown promise as a relatively simple method for waveform-stable MIR generation. Such sources offer tens-of-mW level MIR output powers with a super-octave spectral coverage [28,29,[39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%